Changes in trophic ecology of fish assemblages after no take Marine Protected Area designation in the southwestern coast of Portugal. - Pereira, T.J. (2017)
Changes in fish assemblage structure caused by human activities, such as fishing, can alter trophic relations in fish assemblages. In this context, Marine Protected Areas (MPA) are efficient tools for habitat recovery and ideal environments for evaluating changes on the trophic structure resulting from human activities. The present work targeted fish assemblages from two no-take MPAs from the northern half of South Alentejo and Costa Vicentina Marine Park, established in 2011. Previous works reported positive effects on local fish assemblages after no-take MPA designation, and it is therefore important to further study its impact on local fish assemblages, especially concerning trophic interactions. Local fish assemblages were sampled (summer 2011, winter 2012, summer 2013 and winter 2013) using trammel nets. Diets were characterized and digestive tract contents of the 10 most abundant fish species were compared between the no take MPAs (treatment) and adjacent areas (controls), and changes evaluated as a function of time since protection. Results revealed significant differences between the diets of fish from protected and non protected areas, with crabs being the preferential prey in both protected and control areas but being more ingested outside the no-take areas. However, these differences were evident since the beginning of the study. Fish assemblages from the northern area presented significantly larger niche breadth and significantly increasing with time. This way, the main effects of no-take MPA implementation were directly visible on the niche breadth but did not directly impact the diet composition of the sampled fish assemblages, contributing however to reinforce the already naturally existent differences. This work provides important information regarding the effect of changes in the fish assemblage caused by MPA designation on the trophic ecology of fish.